DEVELOPMENT OF SELF-DETERMINATION AS A KEY FACTOR IN CAREER PLANNING FOR VOCATIONAL HIGH SCHOOL STUDENTS - Hasyim, Wahid (International Journal of Social Service and Research, 2025)
This study aims to explore how students can maximize self-determination to achieve clear career directions. The methodology of this study is designed to provide significant insights that can inform the development of more effective educational programs at the vocational level. The subject of the study was grade XII students at SMKN 1 Mantangai, selected through purposive sampling, with a sample of 20 students relevant to the study's focus. Data collection was carried out through observation and semi-structured interviews. The results show that students' career planning is influenced by their intrinsic motivation, self-reflection methods, and social support. This research provides a basis for designing more effective career guidance programs in vocational schools.